Preliminary Investigation on Vacancy Filling by Small Molecules on the Performance of Dye-Sensitized Solar Cells: The Case of a Type-II Absorber - Asiam, Francis Kwaku; Hao, Nguyen Huy; Kaliamurthy, Ashok Kumar; Kang, Hyeong Cheol; Yoo, Kicheon; Lee, Jae-Joon (Frontiers in Chemistry, 2021)
The steric shielding offered by sensitizers on semiconducting surfaces as a result of branching in the dyes used, offers the less utilization of semiconducting substrate sites during device fabrication in dye-sensitized solar cells (DSSCs). This work proposes a strategy to increase the coverage through the utilization of small molecules which have the ability to penetrate into the sites. The small molecule plays the dual role of vacancy filling and sensitization which can be viewed as an alternative also to co-sensitization. Hence, we show for the first time ever, that the co-adsorption of catechol with Z907 as a sensitizer enhances the electron density in the photo anode by adsorbing on the vacant sites. Catechol was subsequently adsorbed on TiO2 after Z907 as it has a stronger interaction with TiO2 owing to its favorable thermodynamics. The reduced number of vacant sites, suppressed charge recombination, and enhanced spectral response are responsible for the improvement in the PCEs. Quantitatively, both organic and aqueous electrolytes were used and the co-sensitized DSSCs had PCE enhancements of 7.2% and 60% respectively compared to the control devices.